Experiments for combustion temperature measurements in a sugarcane bagasse large-scale boiler furnace - Salinas C.T. (2020)
This work presents a numerical and experimental study to measure local combustion temperature from the combustion reactive zone in an industrial sugarcane. A bagasse boiler furnace is utilized preliminary step towards obtaining online three-dimensional temperature measurements. Two different methods were used for in situ measurement of local temperatures in a sugarcane bagasse flame: Spectral Analysis and Image Processing in the Visible Spectrum. The maximum instantaneous temperatures found in the focused reactive zone area of the bagasse flame were 1623 K and 1520 K by the spectrometric and imaging system respectively and the time average maximum flame temperatures measured were 1443 K and 1496 K. Additionally, a set of flame temperature measurement tests was carried out in a laboratory furnace by the spectrometric method and a time average flame temperature of 1569 K was noted. The flame temperatures found in this work show reasonable agreement with results of CFD simulations and results obtained in laboratory tests which were also reported in the literature. Intensity of emission lines of alkali metal (K) were measured in the flame spectra during the bagasse combustion. Spectral flame emissivity was estimated for an industrial level operating condition. © 2020 Elsevier Ltd